The effects of anxiety on practice behaviors and performance quality in expert pianists - Passarotto, Edoardo; Worschech, Florian; Altenmüller, Eckart (Frontiers in Psychology, 2023)
During their career, musicians need to undergo intense periods of training to master musical instruments and become accomplished artists. Dysfunctional practice behaviors and anxiety are often mentioned among the possible risk factors for playing-related injuries in musicians. However, the mechanism through which these might lead to the onset of these injuries is still unclear. The present study aims at overcoming this limitation by exploring the relationship between practice behaviors and anxiety: it investigates whether anxious musicians practice longer, employ more repetitions and improve at a slower pace than their less anxious colleagues. The experiment consisted in monitoring practice behaviors in 30 pianists practicing a short musical task. Most self-report anxiety measurements were positively correlated with practice time, especially those collected right before the practice sessions. Similar correlations were identified between anxiety and the number of repetitions of the musical task. Physiological markers of anxiety were only weakly related to practice behaviors. Subsequent analyses showed that anxiety impaired performance quality but did not affect the rate at which participants improved in the experiment. Moreover, anxiety and performance quality co-developed during practice sessions, showing that pianists who improved their playing were also less anxious in the latter part of the experiment. These findings suggest that anxious musicians are likely at higher risk of developing playing-related injuries related to overuse and repetitive strains. Future directions and clinical implications are discussed.